The Effect of Global Diversification, Exchange Rates, and Interest Rates on the Performance of Mixed Mutual Funds in Indonesia - Maria Yovita R Pandin; Alif Fa’is Nurfadila; Ahmad Fauzan Aditama; Dewa Wahyu Ananta; Rio Anggara Putra; Anas Ramdani Putra Kurnaedi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of global diversification, exchange rates, and interest rates on the performance of mixed mutual funds in Indonesia during the period 2020–2024. The method used is a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique, using secondary data from the Financial Services Authority, Bank Indonesia, and Bareksa. The sample consists of three mixed mutual fund products that meet the criteria of portfolio data completeness, net asset value, and performance report publication. The results show that exchange rates have a positive and significant effect on mutual fund performance, indicating that exchange rate fluctuations play an important role in determining changes in portfolio returns. The global diversification variable proved to have no significant effect, illustrating that exposure to international markets has not provided stable benefits in improving the performance of mixed mutual funds. Interest rates also did not show a significant effect because the composition of mixed portfolios was able to withstand the impact of monetary policy changes. Simultaneously, the three independent variables were able to explain 66.7 percent of the variation in mixed mutual fund performance, indicating that macroeconomic dynamics and portfolio strategies have an important contribution in influencing the performance of this collective investment instrument.